The smear : how shady political operatives and fake news control what you see, what you think, and how you vote - Attkisson, Sharyl, 1961- (New York : Harper, an imprint of HarperCollinsPublishers, 2017)
"Behind most major political stories in the modern era, there is an agenda; an effort by opposition researchers, spin doctors, and outside interests to destroy an idea or a person. The tactic they use is the Smear. Every day, Americans are influenced by the Smear without knowing it. Paid forces cleverly shape virtually every image you cross. Maybe you read that Donald Trump is a racist misogynist, or saw someone on the news mocking the Bernie Sanders campaign. The trick of the Smear is that it is often based on some shred of truth, but these media-driven 'hit pieces' are designed to obscure the truth. Success hinges on the Smear artist's ability to remain invisible; to make it seem as if their work is neither calculated nor scripted. It must appear to be precisely what it is not."--
Includes index.
Birth of the modern smear: spies, Bork, and the Clintons -- David Brock's smear frontier -- The smear industrial complex: smear merchants and scandalmongers -- Media matters (but money matters more) -- Plausible deniability: conjuring an Astroturf reality -- Transactional journalism: the black market information trade -- the anti-smear candidate (and the disloyal opposition) -- The road to the conventions -- General election -- Brave new world of #FakeNews (and chilling efforts to censor it) -- Epilogue: The smear gone global.
Keywords: Journalism -- Corrupt practices; Mass media and public opinion -- United States; Mass media -- Political aspects -- United States; Communication in politics -- United States; Politics and culture -- United States